International approaches to prostitution : law and policy in Europe and Asia - Gangoli, Geetanjali; Westmarland, Nicole (Policy Press, 2006)
What is to be done about prostitution? Is it work or is it violence? Are women involved in prostitution offenders or victims? Is prostitution a private or a political issue? The answers to these questions vary depending on many factors, including where in the world you live. This book provides a valuable, detailed international comparison of the laws, policies and interventions in eight countries across Europe and Asia.